Nedaplatin/Gemcitabine Versus Carboplatin/Gemcitabine in Treatment of Advanced Non-small Cell Lung Cancer: A Randomized Clinical Trial - Yang, Jin-ji; Zhou, Qing; Liao, Ri-qiang; Huang, Yi-sheng; Xu, Chong-rui; Wang, Zhen; Wang, Bin-chao; Chen, Hua-jun; Wu, Yi-long (Chinese Journal of Cancer Research; Vol 24, No 2 (June 29, 2012): Chinese of Journal Cancer Research, 2012)
Objective: To evaluate the efficacy and safety of nedaplatin/gemcitabine (NG) and carboplatin/gemcitabine (CG) in the management of untreated advanced non-small cell lung cancer (NSCLC). Methods: Sixty-two patients with previously untreated advanced NSCLC were recruited between June 2006 and November 2007. Subjects were randomly assigned to the NG arm (n=30) and the CG arm (n=32). Only patients (24 and 25 in the NG and CG arms, respectively) who completed ≥2 chemotherapy cycles were included in the data analysis. The primary outcome measure was the objective response rate (ORR). The secondary outcome measures included progression-free survival (PFS), overall survival (OS) and adverse events. Results: There were no statistically significant differences in the efficacy measures (ORR, P=0.305; median PFS, P=0.198; median OS, P=0.961) or in the major adverse events (grade 3/4 neutropenia, P=0.666; grade 3/4 anemia, P=0.263; grade 3/4 thrombocytopenia, P=0.212) between the two treatment arms. However, there was a trend towards higher ORR (37.5% vs. 24.0%), longer PFS (6.0 vs. 5.0 months), and less adverse events in the NG arm. Conclusion: NG regimen seems to be superior over CG regimen for advance NSCLS, but further investigation is needed to validate this superiority.